Governance in the Patrimonial State: reference to the venezuelan case (Revista Científica Compendium, 2019)
This essay addresses the determinants of Governance in the so-called Patrimonial State, having as a reference the Fiscal State, with particular reference to the Venezuelan case. Through documentary research, it seeks to show that the emergence and subsequent maturation of a State with its own income was possible thanks to the international oil income, which gives it financial autonomy and a maneuvering capacity to concentrate and centralize power, moving away from democratic guidelines. The entropy resulting from relations without counterweights and the reduction of oil revenues threaten the financial sustainability and viability of the group's political hegemony as government. According to the thesis, the economic-political crisis, that takes place in the second decade of the present century, finds explanation in the contradiction between some norms and institutions designed for a Patrimonial State that struggles to maintain itself and a precarious financial base, characteristic of the Fiscal State.
Keywords: Governance; Fiscal State; Patrimonial State